Book review: Amir, L. B. (2014). Humor and the Good Life in Modern Philosophy: Shaftesbury, Hamann, Kierkegaard. Albany, NY: State University of New York Press. 393 pp. - Andrzej Pawelec (The European Journal of Humour Research, 2015)
Humour as a supreme virtue